2023
DOI: 10.1039/d3qi00683b
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in ammonia synthesis based on photoelectrocatalysis

Abstract: Photoelectrocatalytic (PEC) ammonia synthesis from nitrogen and water is a promising approach in energy development and N-neutralization under mild conditions. Despite significant progress has been made in the past few...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 147 publications
(184 reference statements)
0
6
0
Order By: Relevance
“…Single-atom catalysts (SACs) with an isolated metal atom coordinated on a carbon substrate have recently been demonstrated to deliver superior performance in various electrocatalysis fields, such as the oxygen reduction reaction, hydrogen evolution reaction (HER), and carbon dioxide reduction reaction. 17–22 The maximum atom-utilization efficiency, together with the unique electronic structure and coordination environment, have been proven to contribute to the high activity and selectivity. 23–26 However, for efficient NRR as a multi-intermediate reaction, any ambition by SACs with a monotonous active site seems to be in vain.…”
Section: Introductionmentioning
confidence: 99%
“…Single-atom catalysts (SACs) with an isolated metal atom coordinated on a carbon substrate have recently been demonstrated to deliver superior performance in various electrocatalysis fields, such as the oxygen reduction reaction, hydrogen evolution reaction (HER), and carbon dioxide reduction reaction. 17–22 The maximum atom-utilization efficiency, together with the unique electronic structure and coordination environment, have been proven to contribute to the high activity and selectivity. 23–26 However, for efficient NRR as a multi-intermediate reaction, any ambition by SACs with a monotonous active site seems to be in vain.…”
Section: Introductionmentioning
confidence: 99%
“…The development of effective electrocatalysts by adopting an energy-saving and environmentally friendly method has paved the way for electrochemical N 2 reduction reaction (NRR) as a clean and sustainable alternative technique for the synthesis of NH 3 at more benign conditions. Nevertheless, proficient electrocatalysts are required for the electrocatalytic NRR in order to easily activate the strong N 2 triple bond as well as suppress the competing hydrogen evolution reaction (HER), which in turn can boost up the yield as well as Faradaic efficiency (FE) of NRR …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a wide range of transition metals and nonprecious metal-based hybrid materials have been developed for electrocatalytic HER and oxygen evolution reaction (OER) water splitting. [29][30][31][32][33][34][35][36][37] In the present work, low content of nickel (Ni) and Pt NPs decorated CNF (Ni-Pt/CNFs) were prepared using a simple and efficient approach that combines electrospinning and calcination process. Morphological and energy dispersive X-ray (EDX) analysis revealed that the low content of Ni-Pt NPs is dispersed on the CNF surface.…”
Section: Introductionmentioning
confidence: 99%